High-Efficiency Lithium Niobate Electro-Optic Modulator with Barium Titanate Cladding on Quartz - Hongkang Liu; Jianping Li; Weiqin Zheng; Zixin Chen; Jianbo Zhang; Yuwen Qin (Photonics)
The thin-film lithium niobate (TFLN)-based electro-optic (EO) modulator is one of the most important devices for optical communications in terms of the advantages of low voltages and large bandwidth. However, the large size of devices limits their applicability in large-scale integrated optical systems, posing a key challenge in maintaining performance advantages under restricted design space. In this paper, we propose a novel TFLN modulator on a quartz substrate incorporating barium titanate (BaTiO3, BTO) as the cladding material. The device is designed with silicon–lithium niobate (Si-LN) hybrid waveguides for operation at a wavelength of 1.55 µm. After theoretical analysis and parameter optimization, the proposed 10 mm long modulator demonstrates high-efficiency modulation, featuring a low half-wave voltage-length product of 1.39 V·cm, a broad 3 dB EO bandwidth of 152 GHz, and low optical loss. This theoretical model provides a novel design solution for TFLN modulators on quartz substrates. Moreover, it is a promising solution for enhancing the integration of photonic devices on the TFLN platform.